Respuesta :

Answer:

x= 3

y= 2

Step-by-step explanation:

The given equations are :

2x-5y = -4    equation 1

x +6y = 15    equation 2

We will multiply the equation:2 by 2

2(x+6y=15)

2x+12y=30   equation 3

Lets call this equation:3

Now we will use the elimination method:

Subtract equation 3 from equation 1:

2x-5y = -4

2x+12y=30

_________

   -17y = -34

y= -34/-17

y = 2

Now put the value of y in any equation:

We will use equation 1

2x-5y = -4

2x-5(2)= -4

2x-10= -4

Move the constant to the R.H.S

2x= -4+10

2x=6

Divide both the terms by 2

x= 3

Therefore the solution set is (x,y){(3,2)}....